Histochemical study of the intestinal absorption, liver and lens effect with zinc‐supplemented diets for gilthead seabream. (12th August 2018) - Castro, Pedro L.; Ginés, Rafael; Dominguez, David; Rey, Elvira; Robaina, Lidia; Karalazos, Vasileios; Izquierdo, Marisol
Abstract: To describe the effect and the distribution of zinc in different tissues of a representative marine fish species, gilthead seabreams ( Sparus aurata Linnaeus, 1758) were fed different diets containing zinc in different sources (organic, inorganic, encapsulated, blood‐rich diet or fishmeal). The effect was monitored by histology in the lens, liver and intestine. In addition, the anterior and posterior intestine was studied by means of autometallography, a histochemical silver‐based staining method to determine the zinc flow and distribution. The histology of lens did not improve by dietary zinc as there was no occurrence of cataracts. In the liver, the experimental diets were correlated with different changes in the tissue architecture. In the intestine, no histological changes were found using haematoxylin and eosin stain. However, with the use of autometallography stain, it was possible to visualize and describe the route that zinc follows through the enterocytes and the lamina propria. Organic and inorganic zinc diet produced the richest silver deposition in the anterior intestine.